Clinical sequelae of 17 cases with glycogen storage disease type II/Pompe disease - Zhang, Han-bing (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: To analyze and summarize the characteristics of glycogen storage disease type II (Pompe disease) patients according to the clinical description and prognosis